PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 8 TITI AKAR - Fahrurrozi, Fahrurrozi; Lazim N, Lazim N; Antosa, Zairul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This Study In Carried Out Because The low the Results of Learning IPA Students Of Class IV SDN 8 Titi Akar. Of those 20 Students, Only Nine People Reaching The Leve of Mastery of learning Matrerials, In Accordance with the minimum completeness criteria (KKM) Applied in School, which is 70 and above. Thus. The science lerning that has been implemented is said not to succeed. Because in classical students are required to complete 63,88% to the top. To overcome this problem researchers apply the cooperative learning model type the purpose of this research is to improve scence learning out comes grade 4 SDN 8 Titi Akar. The resuits of the data analysis to know the value of the average silverback base 63 is increased in cycle 1 to 67. In cycle 2 the average value of the average also in creased to 88. On the score to the beginning of the classical completeness learning model type think pair share in cycle I the classical completeness of student learning out comes to be 65 and on the 2nd sycle classical completeness learning out comes of students increased to 100. In cease in the percentage of silver baclk activities of category in creased to 95% in very good category. Nexs on the activity of students also increased the percentage of score activites students 45% with the category less be 95% at the end of cycle II. An increasing the ctivity of students also accompanied by an increase in the study students of 67 with the category of good. And analysis results in the study can conclude that the implementation of learning model Cooperative type thnk pair share (TPS) can improve results learn IPA students of class 4 SDN 8 Titi AkarKeywords: model of learning coopertive type TPS, the results of learning IPA